Anak Petani Tidak Ingin Jadi Petani (Studi di Desa Sesulu Kecamatan Waru Kabupaten Penajam Paser Utara) - Geornes, Ricky; Abdullah, Zulkifli (Citra Media Publishing, 2025)
This research aims to find out the reasons and find out what factors cause farmers' children not wanting to become farmers in Sesulu Village, Waru District, North Penajam Paser Regency. This research uses qualitative methods, collecting data through observation, interviews and documentation techniques. Data sources consist of primary and secondary data, which are analyzed by means of data reduction, data presentation, and then drawing conclusions. The results of the research state that why children of farmers refuse to become farmers in Sesulu Village is because the community considers the farming profession to be the lowest profession. If the new generation chooses farming as their profession, they will not be better than the previous generation or will not experience upward vertical mobility. Children of farmers in Sesulu Village refuse to become farmers due to many factors. In sustainable livelihoods, there are 5 assets that must be fulfilled in order to achieve a sustainable life. There are 3 assets that are factors in farmer children refusing to become farmers, namely social capital, human capital and financial capital. The people of Sesulu Village rarely socialize, farmers are at an unproductive age and people are pessimistic about the finances of the farming profession. Apart from the 3 assets that are not met, there are other factors such as the stigma that farming is a dirty job and farmers' income is uncertain.